Epinephelus akaara fry cultivation method - WANG LU; YU HONG; SHAO YANXIANG; YAN GUOJIANG; ZHANG CHUNLU; SUN SHUGUANG; CHEN CHAO; LI YANLU (2016)
The invention relates to an epinephelus akaara fry cultivation method and belongs to a sea water fish fry cultivation technology. The epinephelus akaara fry cultivation method comprises the following steps: 1) parent fish selection; 2) artificial spawning; 3) spawn distribution; 4) water quality regulation and control; 5) water renewal; 6) feeding. The invention adopts the technical scheme that on the basis of imitating a wild ecological environment, physical and chemical factors are properly adjusted to better adapt to the growth and the development of larvae and juveniles, so that the large-scale cultivation of epinephelus akaara fries is realized. 种赤点石斑鱼苗种培育方法，本发明属于海水鱼类苗种培育技术，它的培育方法步骤包括：1)挑选亲鱼，2)人工催产，3)布卵，4)调控水质，5)换水，6)投喂；本发明技术方案在模仿野生生态环境的基础上，对些理化因子做适当的调整以更适应仔稚鱼的生长发育，实现了大规模化培育赤点石斑鱼苗种。